2022
DOI: 10.1002/jpln.202100133
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur fertilization strategy affects grass yield, nitrogen uptake, and nitrate leaching: A field lysimeter study#

Abstract: Background Globally and at the European Union level there are mounting concerns regarding nitrogen (N) losses from agricultural systems and pressure to reduce N losses to water and air. Suboptimal plant sulfur (S) availability can reduce plant N efficiency and thereby increase N loss potential. Climate change action demands lower sulfur dioxide emissions thus S deposition levels are at an all‐time low. Aims The objectives of the current study were to (1) determine the potential for adequate S nutrition to incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…This effect represented a significant 121% increase in the agronomic efficiency of the N applied as NH 4 NO 3 (+). Although Ca and S are essential nutrients for plants, they are often neglected when considering the fertilization of pastures [32,33]. According to Jones and Ryan [34], soil acidification impacts approximately 30% of the potential food production area globally, with these soils generally deficient in calcium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect represented a significant 121% increase in the agronomic efficiency of the N applied as NH 4 NO 3 (+). Although Ca and S are essential nutrients for plants, they are often neglected when considering the fertilization of pastures [32,33]. According to Jones and Ryan [34], soil acidification impacts approximately 30% of the potential food production area globally, with these soils generally deficient in calcium.…”
Section: Discussionmentioning
confidence: 99%
“…According to Jones and Ryan [34], soil acidification impacts approximately 30% of the potential food production area globally, with these soils generally deficient in calcium. Furthermore, we are currently experiencing a period of relatively low S deposition via precipitation compared to the past, with soil S deposition levels reaching historic lows [32]. This implies reduced synergies between nutrients in the soil, resulting in an imbalance that affects N use efficiency and thus compromises the sustainability of agroecosystems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cysteine, participating in the formation of disulfide bonds between adjacent chains of polypeptides of the gluten complex, plays a key role in shaping its spatial structure [202]. Hence, such a decrease in sulfuric amino acids consequently reduces the rheological parameters of wheat dough, negatively affecting its viscoelastic properties [203]. This was confirmed by Järvan et al [204], who observed an increase in the contents of cysteine and methionine, as well as threonine and lysine, in response to an increase in sulfur supply.…”
Section: Influence Of Sulfurmentioning
confidence: 99%
“…Visual signs of S deficiency in several crops have been discovered lately because of the decreased atmospheric SO 4 2À deposition and increasing purity of fertilizers (Brady and Weil 2004). As a result, research was conducted to determine recommended S rates for various crops with changing S availability (Aspel et al 2022;Inal et al 2003;Mullins 1998;Wysocki et al 2013). However, because S has a strong relationship with other nutrients, it is necessary to investigate the S rate and sources to improve nutrient use efficiency (Chien et al 2011).…”
mentioning
confidence: 99%